Students’ Perception toward English Speaking Motivation during Online Learning System through Multimodal Approach - Usman Sidabutar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
Education is emphasized to grow the tools offered by the 4.0 to create the teaching-learning process more practical and adapted to the social demands. This research aims at finding the students' perception on the teaching method by multimodal approach which is focused on the construction of verbal texts and visual texts. The subject of this research is the students of the sixth semester in English Department of the HKBP Nommensen University Medan. This experiment research is applied by multimodal approach which is focused on the construction of verbal texts and visual texts and continued by questionnaires. The implementation of teaching with a multimodal approach which is focused by verbal and visual tends to motivate students’ interest in speaking English. The result of the score achieved by the students with 73.33 percent is relevant to the students’ motivation with 86.67 percent by the mean of test score in 76.73. This is the one of evidence shows that creativity of the lecturer by multimodal approach by which the digital play makes a huge manner in the interest subject to be lectured.